Spinal subarachnoid haematoma after spinal anaesthesia: case report - Vidal,Marion (2016)
Abstract Subarachnoid haematoma after spinal anaesthesia is known to be very rare. In the majority of these cases, spinal anaesthesia was difficult to perform and/or unsuccessful; other risk factors included antiplatelet or anticoagulation therapy, and direct spinal cord trauma. We report a case of subarachnoid haematoma after spinal anaesthesia in a young patient without risk factors.